Cognitive Behavior Therapies (CBT) in Childhood and Adolescent Mood Disorders and Anxiety Disorders: A Review - Nilgün Öngider (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
In this study, it is aimed to review efficacy of Cognitive Behavioral Therapy (CBT) and Cognitive Behavioral Group Therapy (CBGT) on childhood and adolescence in mood and anxiety disorders. Many researches have shown that cognitive behaviour therapy (CBT) can be effective in the treatment of depression and anxiety in children and adolescents. Child and adolescent depression and anxiety are frequent disorders which may have a recurring and chronic course. PsycINFO, Medline and the Turkish Psychiatric databases were searched, using the key words ‘depressive disorder’, ‘anxiety disorders’ ‘cognitive behavioural treatment’. Then, the journals were examined which had been published in recent years. Individual cognitive behavioral therapy (ICBT) and group cognitive behavioral therapy (GCBT) are the treatment options whose efficacies have been proven in the treatment of depression and anxiety in children and adolescents. Furthermore, some cognitive behavioral therapy-based programs such as “Coping Cat”, “Coping Koala”, “FRIENDS” and family anxiety management programs, have been used among depressive and anxious children and adolescents. Currently, there are different treatment options like computer-assisted cognitive behavioral therapy, computer-based cognitive behavioral therapy and also, internet-based CBT. However, preliminary evidence suggests that computerised cognitive behaviour therapies (cCBT), are acceptable and effective interventions for children and adolescents. In this study is to review not only the effectiveness of cognitive behaviour treatments of depression and anxiety in children and adolescents but also the tecniques which have been used and their effects on the course and the treatments. [JCBPR 2014; 3(2.000): 99-108]